1994
DOI: 10.1111/j.1749-7345.1994.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Feeding of Tilapia in Fertilized Ponds

Abstract: The addition of feed to fertilized fish ponds was evaluated by adding feed alone, feed plus fertilizer, or fertilizer alone to nine ponds stocked with Nile tilapia Oreochromis niloticus. Two experiments were conducted. The first had 500 fish per 250 m2 pond in 3 treatments: ad‐libitum feeding; fertilizer only; or fertilizer and ad‐libitum feeding. The second experiment had 5 treatments with 750 fish per pond ad‐libitum feed only; fertilizer only; or 0.25, 0.50, and 0.75 satiation ration plus fertilizer. Ponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 6 publications
8
50
1
7
Order By: Relevance
“…Moreover, hormone treatment can increase the SGR and DWG of the fish. Similar values of individual growth for monosex tilapia, as in our study, were also observed by Diana et al (1991Diana et al ( , 1994. It has been observed that for a given food composition, the body protein percentage on a wet weight basis is mainly affected by the body weight in salmonids (Shearer 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, hormone treatment can increase the SGR and DWG of the fish. Similar values of individual growth for monosex tilapia, as in our study, were also observed by Diana et al (1991Diana et al ( , 1994. It has been observed that for a given food composition, the body protein percentage on a wet weight basis is mainly affected by the body weight in salmonids (Shearer 1994).…”
Section: Discussionsupporting
confidence: 89%
“…The higher growth rates of control males compared to control females (Table 1) might be due to increased energy being channeled towards metabolic maintenance and somatic growth in males while the females use considerable energy for spawning (Tran-Duy et al 2008). The growth curves of mixed-sex and monosex fish in cages were more or less linear ( Figure 1A) indicating that the critical standing crop in cages was not exceeded (Diana et al 1994) possibly due to the addition of supplemented food. A few studies have demonstrated the enhanced yield of monosex male Nile tilapia populations under experimental conditions (Mair et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam koi increased the SGR and daily weight gain of the fish. Similar values of the individual for Vietnam koi as in the study were also observed by Diana et al [47].…”
Section: Discussionsupporting
confidence: 91%
“…En otros estudios se ha tratado de incrementar la producción acuícola mediante la combinación adecuada de fertilización, alimento balanceado y/o granos (Diana et al, 1994;Green et al, 2002;Liti et al, 2006). Sin embargo, prácticamente no se ha evaluado el efecto productivo de reducir el uso del alimento balanceado complementado con alimentos de origen vegetal y de forma cruda, a baja escala.…”
Section: Introductionunclassified